Effect of substituting IPV for tOPV on immunity to poliovirus in Bangladeshi infants: An open-label randomized controlled trial. Issue 3 (12th January 2016) - Mychaleckyj, Josyf C.; Haque, Rashidul; Carmolli, Marya; Zhang, Dadong; Colgate, E. Ross; Nayak, Uma; Taniuchi, Mami; Dickson, Dorothy; Weldon, William C.; Oberste, M. Steven; Zaman, K.; Houpt, Eric R.; et al.
Highlights: We tested two poliovirus vaccination regimens substituting IPV for the 4th EPI tOPV dose. Neither regimen gave superior intestinal mucosal immunity measured by 1-year poliovirus shedding. The two regimens were equivalent within a 95%CI margin of prevalence of shedding of −10% to +4%. Results for shedding analyses stratified by poliovirus type were similar. IPV regimen strongly enhanced humoral immunity with higher sero-prevalence and -conversion. Abstract: Background: The Polio Endgame strategy includes phased withdrawal of oral poliovirus vaccines (OPV) coordinated with introduction of inactivated poliovirus vaccine (IPV) to ensure population immunity. The impact of IPV introduction into a primary OPV series of immunizations in a developing country is uncertain. Methods: Between May 2011 and November 2012, we enrolled 700 Bangladeshi infant-mother dyads from Dhaka slums into an open-label randomized controlled trial to test whether substituting an injected IPV dose for the standard Expanded Program on Immunization (EPI) fourth tOPV dose at infant age 39 weeks would reduce fecal shedding and enhance systemic immunity. The primary endpoint was mucosal immunity to poliovirus at age one year, measured by fecal excretion of any Sabin virus at five time points up to 25 days post-52 week tOPV challenge, analyzed by the intention to treat principle. Findings: We randomized 350 families to the tOPV and IPV vaccination arms. Neither study arm resulted in superior intestinal protection at 52 weeks measured by the prevalence of infants shedding any of three poliovirus serotypes, but the IPV dose induced significantly higher seroprevalence and seroconversion rates. This result was identical for poliovirus detection by cell culture or RT-qPCR. The non-significant estimated culture-based shedding risk difference was −3% favoring IPV, and the two vaccination schedules were inferred to be equivalent within a 95% confidence margin of −10% to +4%. Results for shedding analyses stratified by poliovirus type were similar. Conclusions: Neither of the vaccination regimens is superior to the other in enhancing intestinal immunity as measured by poliovirus shedding at 52 weeks of age and the IPV regimen provides similar intestinal immunity to the four tOPV series, although the IPV regimen strongly enhances humoral immunity. The IPV-modified regimen may be considered for vaccination programs without loss of intestinal protection.